Association of early life factors with dyslipidemia in children and adolescents: The CASPIAN-V study - Bahareh Vard; Arefeh Adham; Roya Riahi; Golgis Karimi; Mohammad Esmail Motlagh; Ramin Heshmat; Mostafa Qorbani; Roya Kelishadi (Tabriz University of Medical Sciences, 2020)
Background: This study aimed to investigate the association between prenatal/infancy factors and lipid profile in children and adolescents. Methods: This multicentric national study was conducted in 30 provinces in Iran. It comprised4200 participants, aged 7-18 years, from the fifth survey of a national surveillance program. History regarding birth weight, as well as the type of consumed milk and food during infancy was obtained from parents. In addition to physical examinations, fasting blood samples were obtained to assess the lipid profile of these students. Results: Data from 3844 participants were available (91.5% participation rate), 52.4 % of students were boys. Mean (SD) age of participants was 12.3(3.2) years. Consuming cow milk in the first two years significantly increased the risk of high triglycerides (TG) (odds ratio [OR]:2.77, 95% CI: 1.32-5.85, P: 0.01), elevated low-density lipoprotein (LDL) (P<0.05) and low high-density lipoprotein (HDL) (P <0.05). Students who had consumed commercially made food as complementary feeding were 93% more likely to have high LDL (OR: 1.93, 95%CI=1.19-3.13, P: 0.01) and 90% more likely to have high TG than students who had consumed homemade food (OR: 1.90, 95% CI: 1.15-3.12, P: 0.01). The aforementioned figures were not significantly associated with an elevated total cholesterol (TC) level. Conclusion: Our findings revealed that the history of using human milk and home-made food as complementary feeding was associated with better lipid profile in childhood and early adolescence. Increasing public knowledge in this regard might be useful for encouragement of healthier life prevention of chronic diseases.